1998
DOI: 10.1143/jjap.37.l516
|View full text |Cite
|
Sign up to set email alerts
|

Erasable Phase Change Disks with Super Resolution Capability by Pulse-Readout

Abstract: The effect of critical fluctuations in magnetisation near the Curie point and far from the phase transition on the sputtering yield of the magnetic materials Ni and Gd is examined. The inclusion of the spin configuration of the nearest atoms around an atom sputtered from a surface has been found to result in an increase of the target sputtering yield by about 1.5 times compared with the ferromagnetic state.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1999
1999
2001
2001

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…The mechanism of optical superresolution is ascribed to the refraction index of the metal film as a function of temperature 1,2) and the Gaussian intensity distribution of the laser beam. By illuminating a metallic mask film with a focused laser beam, the melting region whose size is much smaller than the focused laser spot size can be well controlled.…”
Section: Principle Of Optical Superresolutionmentioning
confidence: 99%
See 1 more Smart Citation
“…The mechanism of optical superresolution is ascribed to the refraction index of the metal film as a function of temperature 1,2) and the Gaussian intensity distribution of the laser beam. By illuminating a metallic mask film with a focused laser beam, the melting region whose size is much smaller than the focused laser spot size can be well controlled.…”
Section: Principle Of Optical Superresolutionmentioning
confidence: 99%
“…Thus, the two schemes for reducing the focused spot size either have some complications or result in limited performance. The aim of this study is to demonstrate applications of the effect of optical superresolution 1,2) on laser beam writing to effectively reduce the spot size on the PR layer, thus, allowing disk mastering toward higher density using existing light source and optics.…”
Section: Introductionmentioning
confidence: 99%
“…The main functions of the dielectric layers were to prevent material diffusion and to control the cooling rate and reflection coefficient. 1,6) The aluminum (Al) layer functioned as a heat sink and a reflective layer.…”
Section: Principlementioning
confidence: 99%
“…In erasable phase change optical recording, we have reported that diffraction limitation can be circumvented by applying a super resolution technique. 1) Thus, the recording density can be significantly increased at a given laser wavelength and objective NA.…”
Section: Introductionmentioning
confidence: 99%